2019
DOI: 10.1186/s40494-019-0311-9
|View full text |Cite
|
Sign up to set email alerts
|

Fading into the background: the dark space surrounding Vermeer’s Girl with a Pearl Earring

Abstract: The background of Vermeer's Girl with a Pearl Earring (c. 1665, Mauritshuis) has, until recently, been interpreted as a flat dark space. The painting was examined in 2018 as part of the research project The Girl in the Spotlight using a combination of micro-and macro-scale analytical techniques. The stratigraphy of the background was determined from samples mounted as cross-sections, and its material composition was analysed using electron microscopy and chromatographic techniques. The underlayer contains main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(40 citation statements)
references
References 20 publications
2
37
0
1
Order By: Relevance
“…A fragment was analysed using thermally assisted hydrolysis and methylation, pyrolysis gas chromatography-mass spectrometry (THM-Py-GC/MS), which determined that the binding medium of the ground is linseed oil. This confirms the results from the analysis by Groen et al [4], but specified that the linseed oil had been prepared by heating [8].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A fragment was analysed using thermally assisted hydrolysis and methylation, pyrolysis gas chromatography-mass spectrometry (THM-Py-GC/MS), which determined that the binding medium of the ground is linseed oil. This confirms the results from the analysis by Groen et al [4], but specified that the linseed oil had been prepared by heating [8].…”
Section: Discussionsupporting
confidence: 90%
“…This helps to answer the third research question posed by the Girl in the Spotlight project: Which techniques did Vermeer use to create subtle optical effects, including the transition between light and shadow? The role of the underlayers in other areas of the painting are discussed in greater detail in other articles in this digital volume [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Vandivere et al ; c False-colour spectral unmixing map displaying the distribution of fluorescence endmember spectra shown in e, including the 'red' endmember with 620 nm emission peak, the 'blue' endmember with 707 nm emission peak, and the 'green' endmember with a slowly decreasing emission intensity; d raw fluorescence emission spectra from the FIS data cube from which the endmember spectra (e) were calculated to make the map in c; e Endmembers used for spectral unmixing. The 'red' and 'blue endmembers were calculated by subtracting off a scaled spectrum of the component with slowly decreasing emission, shown with a 'green' dashed line [21] determined the composition of this underlayer from three re-analysed cross-sections: it is predominately charcoal, based on the presence of carbon and the appearance of splintery particles. They also confirmed that the glaze in a sample from the lower right-one that was also examined by Groen et al [6]-appears yellowish with transparent blue spots.…”
Section: Introductionmentioning
confidence: 99%
“…8f ). The diagonal lines visible in the lead map has been interpreted as the modelling of a possible draped fabric, such as a curtain [21]. Groen et al [6] reported the presence of a little lead white in the glaze.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation